POLITICAL POEMS BY GOENAWAN: WOMAN READERS' PERCEPTION: PUISI POLITIK OLEH GOENAWAN: PERSEPSI PEMBACA WANITA - Afrini Rahmi; Ria Satini (Jurnal Kata, 2024)
This study investigates the emotional reception of readers towards election-themed poetry by Goenawan Mohamad. It aims to describe the emotional responses elicited by these poems, focusing on the impact of abstract words and figurative language. This literary reception research adopts a synchronic approach using the mixed method. Data were collected from questionnaires distributed to selected respondents and then analysed qualitatively to find meaning.The findings reveal that the use of abstract words and various figures of speech (simile, personification, allegory, litotes, rhetoric, metaphor, and assonance) plays a significant role in shaping the emotional reader. Poetry of Goenawan Mohamad are representing of  loss and anxiety.